Methods to prevent lymphocele after kidney transplantation: seeking the optimal technique for avoiding a preventable complication - Sabagh, Mohammad Sadegh; Sabetkish, Nastaran; Fakour, Sanam; Ramouz, Ali; Weber, Sanaz; Mieth, Markus; Lurje, Georg; Golriz, Mohammad; Zeier, Martin; Mehrabi, Arianeb; Khajeh, Elias (Transplantation reviews, 2024)
Background - There are multiple methods for preventing lymphocele formation after kidney transplantation (KTx). However, lymphoceles still develop in up to one third of patients and the effectiveness of these different methods in preventing lymphocele is not well described. Here, we summarize the current strategies for preventing lymphocele after KTx. - Methods - We conducted searches across several literature databases, including Medline (via PubMed), Web of Science, EMBASE, and Cochrane Central. Lymphocele formation after KTx was the outcome of interest. A random-effects model was applied to evaluate pooled estimates, which were presented as hazard ratios (HRs) and odds ratios (ORs), along with the random pooled estimate (ES), 95% confidence interval (95% CI), and P value. We calculated the pooled rate of lymphocele formation after KTx with the following preventive methods: LigaSure, haemostatic materials, prophylactic drainage, ligation, peritoneal fenestration, and bipolar cautery techniques. - Results - The literature search retrieved 87 unique studies after excluding duplicates. Twenty papers reporting on 5445 patients were incorporated in the qualitative analysis. The pooled lymphocele rate was 3.0% (95% CI = 0.6-13.7) for the LigaSure method, 8.3% (95% CI = 6.4-10.7) for drainage, 9.2% (95% CI = 5.9-14.1) for haemostatic materials, 12.2% (95% CI = 9.2-16.1) for ligation, 14.4% (95% CI = 12.0-17.3) for peritoneal fenestration, and 20.5% (95% CI = 10.2-36.8) for bipolar sealing. - Conclusion - Despite preventive methods, the incidence of lymphocele following KTx remains high. The use of LigaSure appears to be the most effective method for preventing lymphocele. However, given the broad range of reported lymphocele rates and lack of control groups, further validation of these findings is necessary.
Online verfügbar: 7. August 2024, Artikelversion: 13. August 2024
Gesehen am 20.03.2025